2013
DOI: 10.1093/bioinformatics/btt393
|View full text |Cite
|
Sign up to set email alerts
|

Exhaustively characterizing feasible logic models of a signaling network using Answer Set Programming

Abstract: Motivation: Logic modeling is a useful tool to study signal transduction across multiple pathways. Logic models can be generated by training a network containing the prior knowledge to phospho-proteomics data. The training can be performed using stochastic optimization procedures, but these are unable to guarantee a global optima or to report the complete family of feasible models. This, however, is essential to provide precise insight in the mechanisms underlaying signal transduction and generate reliable pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 25 publications
1
52
0
Order By: Relevance
“…Model checking and symbolic reasoning have been used to verify properties of manually constructed biological models , complete partially specified pathways using perturbation data (Köksal et al, 2013), and synthesize gene regulatory networks directly from data (Dunn et al, 2014;Moignard et al, 2015) (reviewed in ). In addition, other types of declarative approaches, such as integer programming (Budak et al, 2015;Chasman et al, 2014;Jain et al, 2016;Ourfali et al, 2007;Sharan and Karp, 2013;Silverbush and Sharan, 2014) and answer set programming (Guziolowski et al, 2013), have been applied to biological pathway analysis. The TPS model summarization strategy, which makes it applicable to comprehensive signaling networks containing more than a hundred thousand edges and phosphosites, sets it apart from these related methods (Supplemental Results and Figure S15).…”
Section: Contrasting Tps With Related Computational Approachesmentioning
confidence: 99%
“…Model checking and symbolic reasoning have been used to verify properties of manually constructed biological models , complete partially specified pathways using perturbation data (Köksal et al, 2013), and synthesize gene regulatory networks directly from data (Dunn et al, 2014;Moignard et al, 2015) (reviewed in ). In addition, other types of declarative approaches, such as integer programming (Budak et al, 2015;Chasman et al, 2014;Jain et al, 2016;Ourfali et al, 2007;Sharan and Karp, 2013;Silverbush and Sharan, 2014) and answer set programming (Guziolowski et al, 2013), have been applied to biological pathway analysis. The TPS model summarization strategy, which makes it applicable to comprehensive signaling networks containing more than a hundred thousand edges and phosphosites, sets it apart from these related methods (Supplemental Results and Figure S15).…”
Section: Contrasting Tps With Related Computational Approachesmentioning
confidence: 99%
“…Answer Set Programming (ASP) [10] is an active research area of artificial intelligence. It provides a logic-based declarative modelling language and problem solving framework [24] for hard computational problems, which has been widely applied [2,27,40,41]. In ASP, questions are encoded into rules and constraints that form a disjunctive (logic) program over atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Although not shown in this work, we have found that the variability of input-output behaviors is significantly lower than models topologies. Recent advances in this direction and considering real-world experimental data, can be found in [30]. Briefly, in the aforecited work it is shown that if the experimental error is considered, several thousands of Boolean logic models fit the available data similarly well.…”
Section: Resultsmentioning
confidence: 99%